Effects of a diet supplemented with polysaccharides from Pogostemon cablin on growth performance, meat quality, and antioxidant capacity in Chongren Partridge chickens - Tang, Yantian; Chen, Si; Chen, Lingli; Ouyang, Kehui; Chen, Hui; Wang, Wenjun (Frontiers in Veterinary Science, 2024)
In this study, the Pogostemon cablin polysaccharides (PCPs) were heteropolysaccharides with molecular weights of 63.17 kDa and 8.99 kDa, and their total carbohydrate content was 76.17 ± 0.23%, uronic acid content was 19.92 ± 0.42%, and protein content was 1.24 ± 0.07%. PCP is composed of arabinose, galactose, glucose, and glucuronic acid, with a molar ratio of 0.196:0.249:0.451:0.104. In addition, we further investigated the effects of the diet supplemented with different doses of PCP on growth performance, meat quality, and anti-oxidant capacity in Chongren Partridge chickens. A total of 200 chickens were randomly allocated into 4 treatments, and fed with a basal diet of 0 (CON), 200 (LPCP), 400 (MPCP), and 800 (HPCP) mg/kg PCP for a 14-day prefeeding period and a formal experimental period of 56 days. Results showed that dietary PCP significantly increased final body weight (BW), average daily gain (ADG), and decreased feed-to-gain ratio (F/G) from days 1 to 56. Meanwhile, dietary PCP reduced yellowness (b∗) values and increased redness (a∗) values at 24 h in breast muscles (p < 0.05). Furthermore, LPCP and MPCP significantly increased the level of guanylic acid (GMP) (p < 0.05). MPCP increased the content of free amino acids (isoleucine, leucine, lysine, methionine, threonine, valine, alanine, glutamic acid, serine, cysteine), total essential amino acid (EAA), total flavor amino acid (FAA), total AA, the content of fatty acids (c14:1, c16:1, and c22:2), and monounsaturated fatty acids (MUFAs) in the breast muscle when compared to CON (p < 0.05). In addition, MPCP significantly reduced the content of malondialdehyde (MDA) and increased the transcript abundances of fatty acid desaturase 2 (FADS2), fatty acid synthase (FAS), lipoprotein lipase (LPL), and sterol regulatory element binding protein-1 (SREBP-1) in the breast muscles of the chickens (p < 0.05). In light of the aforementioned results, PCP at 400 mg/kg could be used as an effective additive because it not only promotes the growth performance of Chongren Partridge chickens but also shows a conducive role in meat quality, especially in meat flavor.